2022
DOI: 10.1109/access.2022.3204029
|View full text |Cite
|
Sign up to set email alerts
|

GlauNet: Glaucoma Diagnosis for OCTA Imaging Using a New CNN Architecture

Abstract: Glaucoma is a neurodegenerative disease that affects the optic nerve head and causes visual field defect. Current investigations focus on neural component which may overlook other important factors such as the vascular cause. The optical coherence tomography angiography (OCTA) imaging has been developed and provided quantitative parameters that showed good diagnostic accuracy to detect glaucoma. However, those parameters are based on image processing of observed clinical findings, therefore, some image informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Anyone with glaucoma, AMD, or diabetic retinopathy may find the results of this poll very interesting. Anita Manassakorn, Supatana Auethavekiat [19] have assessed CNN's capability to identify glaucoma in OCTA images. They created GlauNet, a specially designed CNN model.…”
Section: Related Studymentioning
confidence: 99%
“…Anyone with glaucoma, AMD, or diabetic retinopathy may find the results of this poll very interesting. Anita Manassakorn, Supatana Auethavekiat [19] have assessed CNN's capability to identify glaucoma in OCTA images. They created GlauNet, a specially designed CNN model.…”
Section: Related Studymentioning
confidence: 99%
“…The output of this process is a sub-image, which is then referred to as an ROI disc. The ROI detection carried out refers to research [4] whose process stages are shown in Figure 2.…”
Section: Pre Processing 1 Region Of Interest (Roi) Disc Detectionmentioning
confidence: 99%